Juridical Study of Application for Rights with Grant Proof Seal for Minors Under Goverment Regulation (PP) No. 24 of 1997 on Land Registration - Suyahmin Suyahmin; Euis Listianti; Amin Purnawan (Jurnal Akta, 2018)
Grants should be made in written form of the Public Notary. Grants will not be made by a Notary who do not have the force of law, they are subject to the customary law may be made under the hand, but the process must be made with the Land Office PPAT deed. In the implementation of the grant, the subject must be an adult (legally competent) so that it can perform its own legal actions because he has the right and obligation in full. The purpose of this study was to analyze the Strength of the Land Law with Proof Seal for Minors under PP 24 of 1997 as well as obstacles and solutions. The research method used juridical empirical approach, with qualitative descriptive data analysis techniques. The results of the research community who received land rights that have been acquired through a grant should make efforts to transition of property rights over land rights in accordance with the procedures and requirements are clear, whose goal in order to have certainty and legal protection for land-rights holders. But in this case the donee legal subjects are people who are still legally minors who have not been capable of doing a legal act.Keywords: Land Registry; Land Grant; Minors.